USE OF FALLEN COCOA PODS BY ANTS (HYMENOPTERA, FORMICIDAE) IN SOUTHEASTERN BRAZIL - Fowler, H. G. (Kansas Entomological Soc, 1993)
Fallen cocoa pods serve as nesting and foraging sites for litter and ground ants in southeastern Brazil. The distribution of the number of species per pod deviated significantly from a Poisson distribution, with a prevalence of one species per pod. Only 17 species of a much larger fauna were present in pods, with the dominant species being Gnamptogenys striatula, and Oligomyrmex sp. Colony populations for 13 species are given.